Analysis of Coupling Strategies for Building Simulation Programs. (November 2015) - Vanpachtenbeke, Michiel; Van De Walle, Wouter; Janssen, Hans; Roels, Staf
Abstract: Although building simulation tools have already proven to be very useful, there still is a lack of a simulation tool taking into account all building physical aspects. To develop such an integrated tool, two approaches are typically suggested: co-simulation and mono-simulation. In the first, the various building physical aspects of a certain problem are modelled in different appropriate state-of-the-art building simulation tools, which are coupled by exchanging intermediate results during simulation time. The main drawback of this technique is a possible negative impact on the accuracy of the results and even on the computational cost when iterating between the different models. Therefore mono-simulation, in which the problem is modelled and simulated in its entirety, is suggested as an alternative to co- simulation. This technique possibly leads to a better accuracy, though a high computational cost is expected due to the resulting largeness of the simulation model. This study aims at assessing the numerical efficiency of these two different approaches for integrated building simulation tools. Co-simulation shows to be a potentially better performing technique, though, its efficiency strongly depends on the applied strategy and the exchange variable.